HUBUNGAN SALES GROWTH DAN EPS GROWTH TERHADAP PERTUMBUHAN HARGA SAHAM - Si Made Ngurah Purnaman (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of revenue and Earnings Per Share (EPS) on stock price growth of technology sector companies listed on the Indonesia Stock Exchange. This study employs secondary data from corporate financial statements and applies panel data regression analysis using the Random Effect Model approach. The results indicate that revenue has a positive but insignificant effect on stock price growth, while EPS has a positive and significant effect on stock price growth. These findings suggest that investors place greater emphasis on profitability indicators rather than revenue growth when evaluating the value of technology sector stocks. This study is expected to provide empirical evidence for capital market research and serve as a reference for investors in making investment decisions. Keywords: Revenue, Earnings Per Share, Stock Price Growth, Technology Sector